Investigation of Time Diversity Gain for Earth to Satellite Link Using Rain Rate Gain - Alam, Md Moktarul; Rafiqu, Islam Md.; Badron, Khairayu; Dyana A. R, Farah; Dao, Hassaan; Hassan, M. Rofiqul; Lwas, Ali Kadhim (Institute of Advanced Engineering and Science, 2019)
The utilization of satellites for communication systems has expanded considerably in recent years. C and Ku-bands of frequencies are already congested because of high demand. Future directions of satellite communications are moving towards Ka and V-bands. Earth to satellite communications are moving towards higher frequency bands in future which are more sensitive to environment. Rain causes severe degradation in performances at higher frequency bands specially in tropical regions. Several mitigation techniques are proposed to design reliable system. Time diversity is one of the potential candidate for it. However, time diversity analysis requires measured rain attenuation data. For future high frequency link design those data are not available at most of the places. This thesis proposes a method to utilize 1-minute rain rate to analyze time diversity technique at any desired frequency. This paper proposes a method to utilize 1-minute rain rate to analyse time diversity rain rate gain. In proposed method, it is assumed that rain rate gain with delay can represent rain attenuation gain with delay for same period of time at same location. The characteristics of rain rate and rain attenuation almost same because the attenuation causes due to rain. One year measured rain rate in Malaysia is used to predict rain rate gain. The measured gain at 12.225 GHz signal is compared with that predicted by ITU-R based on rain rate measurement and is found good agreement. Hence it is recommended that the time diversity gain can be predicted using measured rain rate for any desired frequencies